Ingemar Ståhl 1938-2014. A Portrait of a Political Economist in the Swedish Welfare State - Lars Jonung (Lund University, School of Economics and Management, Department of Economics, 2019)
For many decades, Ingemar Ståhl was a well-known economist in Sweden. He introduced new perspectives into research, teaching and public debate. He made his presence felt in areas as diverse as housing policy, defense economics, energy policy, financial economics, industrial policy, higher education, union controlled wage earner funds, law and economics, health-care economics and taxation. He advocated a public choice perspective which in his view provided a more realistic interpretation of the behavior of politicians and bureaucrats than that provided by traditional welfare economics. As an active participant in the public debate, he provided a pungent commentary on a wide range of issues. He contributed to the shift in Swedish economic policy from interventionist controls and collectivist systems inspired by Social-Democratic ideology to market-oriented and liberal solutions. Several of his proposals, most prominently the present system of student finance remain part of current Swedish public policy.
Keywords: A11; B21; D51; D72; H43; I22; J51; L51; P48; Q18; 330; Public choice; welfare economics; property rights; socialism; liberalism; welfare state; Sweden